2021
DOI: 10.3390/life11020172
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Analysis Identified Key Schizophrenia Risk Factors from an Abnormal Behavior Mouse Gene Set

Abstract: Schizophrenia (SCZ) is a severe chronic psychiatric illness with heterogeneous symptoms. However, the pathogenesis of SCZ is unclear, and the number of well-defined SCZ risk factors is limited. We hypothesized that an abnormal behavior (AB) gene set verified by mouse model experiments can be used to better understand SCZ risks. In this work, we carried out an integrative bioinformatics analysis to study two types of risk genes that are either differentially expressed (DEGs) in the case-control study data or ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“… 35 Variants of the SHANK1 gene have been associated with a spectrum of neurodevelopmental disorders, and neurologic complications are reported to be highly prevalent among PWH and in CKD, irrespective of the cause. 36 , 37 , 38 , 39 This identified signal could be related to the development of neurologic diseases that are common among PWH and in CKD.…”
Section: Discussionmentioning
confidence: 99%
“… 35 Variants of the SHANK1 gene have been associated with a spectrum of neurodevelopmental disorders, and neurologic complications are reported to be highly prevalent among PWH and in CKD, irrespective of the cause. 36 , 37 , 38 , 39 This identified signal could be related to the development of neurologic diseases that are common among PWH and in CKD.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning neuropsychiatric disorders, an integrative multi-omics analysis identified four categories of key genes involved in the pathogenesis of schizophrenia (SCZ), thus offering new insights to better understand the complexity and regional heterogeneity of SCZ [8]. Moreover, another study suggested that the disruption of DGCR8-dependent microRNA biogenesis is crucial for the 22q11.21 copy number variant (CNV) genes involved in psychiatric disorders for late fetal cortical development [9].…”
mentioning
confidence: 99%